The Effect of Using Poster on Students’ Vocabulary Mastery at The Eighth Grade Students of MTs Masyariqul Anwar Caringin Labuan Pandeglang Banten in Academic Year 2021/2022 - Komsah, Ocah; Sudirman, Ade; Gumelar, Rizdki Elang (Journal of English Education Studies, 2022)
This researcher aims to know the effect of poster media on students’ vocabulary mastery at eighth grade students of MTs Masyariqul Anwar Caringin. This research uses quantitative approach, with pre-test and post-test experimental and control group design. The data collecting technique used is triangulation which consists of pre-test, treatment and post-test. The experimental class for this research was VIII E and control class was VIII G. Each class has 30 students, for a total sample is 60 students. The experimental class mean score on the pre-test was 54,60, while the control class mean score on the pre-test was 51,60. On the other hand the post-test result is, the mean score of experimental class was 72,56 while the mean score of control class was 56,53. Hypothesis calculating was done by using SPSS 22 Version. The result obtained from hypothesis test is 0.00 < 0.05 it means that there is significant effect of using poster media to students’ vocabulary mastery at the eighth grade of MTs Masyariqul Anwar Caringin.